2021
DOI: 10.1002/pan3.10234
|View full text |Cite
|
Sign up to set email alerts
|

Reindeer husbandry in peril?—How extractive industries exert multiple pressures on an Arctic pastoral ecosystem

Abstract: Environmental changes and their consequences on biodiversity are known to have far‐reaching effects on the resilience of animal populations and associated livelihoods around the world. To counteract negative demographic and economic effects on pastoralism, knowledge about the historical and current status of the environment is essential. In this study, we show how extractive industries, especially large‐scale mining, induced a cascade of land conversions which are affecting animal populations and pastoralists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 64 publications
(60 reference statements)
0
15
0
Order By: Relevance
“…For the Sa ´mi reindeer herding culture to also flourish in the future, it is pertinent that their adaptive capacity to warmer and more variable weather and snow conditions increases. On the contrary, we observe a continued reduction of the adaptive capacity of Laevas RHC because of an increase of competing land-use activities (Fohringer et al 2021). It is, therefore, pertinent that environmental planning efforts also integrate the effects of climate change on the availability of ecosystems for reindeer grazing.…”
Section: Average Air Temperatures Have Increased In Northernmentioning
confidence: 75%
See 2 more Smart Citations
“…For the Sa ´mi reindeer herding culture to also flourish in the future, it is pertinent that their adaptive capacity to warmer and more variable weather and snow conditions increases. On the contrary, we observe a continued reduction of the adaptive capacity of Laevas RHC because of an increase of competing land-use activities (Fohringer et al 2021). It is, therefore, pertinent that environmental planning efforts also integrate the effects of climate change on the availability of ecosystems for reindeer grazing.…”
Section: Average Air Temperatures Have Increased In Northernmentioning
confidence: 75%
“…On the contrary it is a major concern among all RHC in Sweden, and among herding communities in other Arctic regions (e.g., Lo ¨f et al 2012;Mathiesen et al 2013;Uboni et al 2016). Laevas RHC, however, experiences many additional land-use changes such as infrastructure development associated with the mining industry (LKAB, Laevas-och Gabna samebyar 2015), the relocation of the township of Kiruna (Sjo ¨holm 2013), forestry, and tourism (Fohringer et al 2021). The number of areal and linear infrastructures has increased, and therefore reduced pasture areas and connectivity between remaining pastures over the past 130 years (Fohringer et al 2021).…”
Section: Average Air Temperatures Have Increased In Northernmentioning
confidence: 99%
See 1 more Smart Citation
“…Österlin and Ratio’s (2020) macro-level study of RHCs identified an increase in permits granted for mining (from 1000 ha to over 20 000 ha between 1960 and 2017) and wind turbines (from 48 to 983 operating turbines between 2003 and 2017). Fohringer et al ( 2021 ) focussed on an individual mountain RHC, and their case study concluded that 34% of pasturelands had become functionally unavailable; this can be compared to the case study reported by Kløcker-Larsen et al ( 2016 ), which concluded that 54% of winter pasturelands were within aforementioned disturbance zones. Regarding predator pressure, the Sámi parliament recently reported that, for many RHCs, 20–40% of the herd (mainly calves) was killed by predators annually, which is much higher than the 10% tolerance level defined by the state (Sámediggi 2021b ).…”
Section: The Flux Of Nature: Non-equilibrium Theory and Grazing Dynamicsmentioning
confidence: 94%
“…Encroachment due to competing land uses can remove forage and limit its accessibility. Cumulative effects of encroachments have been analysed using a variety of sector-based economic, GIS and qualitative data (Kløcker-Larsen et al 2016 ; Österlin and Raitio 2020 ; Fohringer et al 2021 ). Österlin and Ratio’s (2020) macro-level study of RHCs identified an increase in permits granted for mining (from 1000 ha to over 20 000 ha between 1960 and 2017) and wind turbines (from 48 to 983 operating turbines between 2003 and 2017).…”
Section: The Flux Of Nature: Non-equilibrium Theory and Grazing Dynamicsmentioning
confidence: 99%